A SENSORY READING OF SPATIAL EXPERIENCE FROM A FILM'S SETTING - Ghina Shofia; Arnis Rochma Harani (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: The purpose of this article is to explore spatial experience through the lens of film settings. Films have been structured to depict a narrative about a space and its experiences to date. There have been few studies examining how a spatial setting in a film can evoke an architectural experience. Through the analysis of sensory-centered experiences derived from spatial settings in films, this paper aims to contribute to the understanding of architecture, particularly the relationship between the body and the space. Using a qualitative approach, this article discusses the film